PENGARUH FAKTOR FUNDAMENTAL DAN FAKTOR TEKNIKAL TERHADAP HARGA SAHAM (STUDI KASUS PADA PERUSAHAAN PROPERTY DAN REAL ESTATE) - Dwi Septa Aryani (Universitas Tridinanti, 2021)
The purpose of this study is to examine the effect of fundamental factors (ROI, DTA, QR) and technical factors (EVA) on stock prices (case studies of property and real estate companies listed on the IDX). The variables used in this study are profitability (ROI), leverage (DTA), liquidity (QR), EVA and stock prices. This study uses statistical eviews. The results showed that simultaneously fundamental and technical factors had an effect on stock prices. The results of the study partially show that only leverage (DTA) has an effect on stock prices. While ROI, QR and EVA have no effect on stock prices.Keywords: ROI, DTA, QR, EVA dan Stock Prices